A Survey of Military Application of Wireless Sensor Networks For Soldiers (International Journal of Engineering and Computer Science, 2018)
Wireless sensor network with a large number of sensor nodes can be used as an effective tool for gathering data in different ways. Wireless Sensor Networks (WSNs) with small nodes can use for sensing, computation, and wireless communications capabilities. Wireless sensor networks (WSNs) are a relatively new and rapidly developing technology; they have a wide range of applications including environmental monitoring, agriculture, public health and detect, identify and track adjacent hostile targets in military environments. In this paper we propose an application of WSNs in military enviroments